Analysis of dielectric properties of cytosine in aqueous solution - Manzur, Maria Eugenia (2001)
The dipole moment of cytosine in dilute aqueous solutions was experimentally determined through permitivity, refraction index and density measurements in order to study the solvent effect on the behaviour of cytosine under the action of a low frequency electric field. Buckingham's equation was used, and μexp = 7.99 D was obtained. A theoretical study was also undertaken which considered cytosine in isolation and in two association models of the solute with four and six molecules of water respectively. The data for the dipole moment as well as an estimation of the hydration energies were obtained from models evaluated at three theoretical levels: Semiempirical calculations (in particular the AM1 method), ab initio calculations at the RHF/6-31+G* level of theory and density functional theory (B3LYP/6-31+G*) for the inclusion of electronic correlation. Although the six water molecule model bonded by hydrogen bonds was shown to be the more stable one, the results of μexp confirm that both intermolecular association models are compatible.